STUDI ANALITIK DAN KOMPUTASI ALIRAN PEMBULUH DARAH PADA BAGIAN UJUNG DAN TENGAH CAROTID BIFURCATION - Hendrarsakti, Jooned; Raymond, Raymond (Bina Teknika, 2018)
One of the most commonly discussed Cardiovascular diseases is a stroke uniform caused by the stagnation of blood flow to the brain due to the narrowing of blood vessels by fat (atheroclerosis). This study examines the effect of reducing the number of lumen areas and the location of the blockage to human blood velocity, pressure, and flow rate by using CFD (Computational Fluid Dynamics). In the modeling stage, 13 kinds of luminal cross-sectional area were collaborated with 2 clogging locations and 1000 calculation was done. From the simulation, results obtained the value of pressure velocity and discharge. From the results show that the value of velocity reaches peak at 28-30% of lumen cross-sectional area and decreases at 30% cross section. The simulated debit values show that the larger the area of the lumen cross section, the higher the flowing blood flow and the opposite. While the analytic results show the value of speed is increasing and the decreasing pressure caused by the reduction of the luminal cross-sectional area, the value of the calculation of the analytic calculation shows the same values